Radial endobronchial ultrasound for the diagnosis of peripheral pulmonary lesions: A systematic review and meta‐analysis. Issue 3 (8th February 2017) - Ali, Muhammad S.; Trick, William; Mba, Benjamin I.; Mohananey, Divyanshu; Sethi, Jaskaran; Musani, Ali I.
ABSTRACT: Tissue diagnosis of peripheral pulmonary lesions (PPLs) can be challenging. In the past, flexible bronchoscopy was commonly performed for this purpose but its diagnostic yield is suboptimal. This has led to the development of new bronchoscopic modalities such as radial endobronchial ultrasound (R‐EBUS), electromagnetic navigation bronchoscopy (ENB) and virtual bronchoscopy (VB). We performed this meta‐analysis using data from previously published R‐EBUS studies, to determine its diagnostic yield and other performance characteristics. Ovid MEDLINE and PubMed databases were searched for R‐EBUS studies in September 2016. Diagnostic yield was calculated by dividing the number of successful diagnoses by the total number of lesions. Meta‐analysis was performed using MedCalc (Version 16.8). Inverse variance weighting was used to aggregate diagnostic yield proportions across studies. Publication bias was assessed using funnel plot and Duval and Tweedie's test. 57 studies with a total of 7872 lesions were included in the meta‐analysis. These were published between October 2002 and August 2016. Overall weighted diagnostic yield for R‐EBUS was 70.6% (95% CI: 68–73.1%). The diagnostic yield was significantly higher for lesions >2 cm in size, malignant in nature and those associated with a bronchus sign on computerized tomography (CT) scan. Diagnostic yield was also higher when R‐EBUS probe was within the lesion as opposed to being adjacent to it. Overall complication rate was 2.8%. This is the largest meta‐analysis performed to date, assessing the performance of R‐EBUS for diagnosing PPLs. R‐EBUS has a high diagnostic yield (70.6%) with a very low complication rate.